CYBERNETIC ANALYSIS: A CASE STUDY OF ONLINE COUNSELLING BY PSYCHOLOGISTS THROUGH THE RILIV APP - Diya, Margareta; Akmalia Apsari, Diani; Putri Cahyandari, Yenika; Eva, Nur; Dharmastuti, Anjarie (Universitas Muhammadiyah Surakarta, 2024)
This study aims to further investigate the effectiveness of online counselling and client satisfaction of RILIV app users. This research uses a cybernetic psychology approach to explore the process of information exchange between psychologists and clients, as well as the trust built through technological intermediaries. The method used in this research is a qualitative method with data collection through interviews. The research subjects included 1 psychologist involved in the RILIV app and 1 client who had received services through the platform. Through cybernetic analysis, the results showed that the cognitive process of information processing plays an important role in the communication process between psychologists and clients. However, challenges in online counselling, such as the lack of signals and the inability to see facial expressions and gestures directly, can affect the effectiveness of cognitive processes. Therefore, effective online counselling requires a careful integration of technology with an approach that takes into account the changing mindsets and reflections of individuals, as well as efforts to overcome communication barriers that may arise in a virtual environment.